Comparison study of the pullout strength of conventional spinal pedicle screws and a novel design in full and backed-out insertions using mechanical tests. (March 2014) - Amaritsakul, Yongyut; Chao, Ching-Kong; Lin, Jinn
Recently, new pedicle screw designs have been developed. However, these designs' performances are still unclear, especially when backed out after insertion. The objective of this study was to investigate the performances of different screw designs when backed out from full insertion. Seven conventional designs of the pedicle screw and one novel design were inserted into polyurethane foam (0.32 g/cm 3 ). All screws were first fully inserted (43 mm) and were backed out 360°. Axial pullout tests were performed and the reaction force was measured. The results showed that the conical screw of type 1 with a small inner diameter provided the highest pullout strength in both full insertion and backed-out insertion (2401.85 and 2169.82 N, respectively). However, this screw's pullout strength significantly decreased (9.7%) when backed out from full insertion. There was no significant difference between the conical screw of type 1 with a small inner diameter and double duo core screw ( p > 0.01) in backed-out insertion. The cylindrical screw with a small diameter, dual inner core screw and double dual core screw also provided good results in both full insertion (2115.44, 2182.99 and 2226.93 N, respectively) and backed-out conditions (2065.80, 2014.28 and 1941.29 N, respectively). The increased pullout strength of the conical design could be due to the effect of bone compaction. However, the screw exhibited less consistent pullout strength when backed out when compared with the other designs. The conical screw should be inserted to the precise position without turning back, especially in osteoporosis patients. The dual inner core screw and double dual core screw could provide greater stability in both conditions. Care should be taken when using both the cylindrical screw with a small thread depth and the dual outer core screw.